Playing for keeps or just playing with emotion? Studying tilt and emotion regulation in video games - Cregan, Sarah C.; Toth, Adam J.; Campbell, Mark J. (Frontiers in Psychology, 2024)
In video gaming, tilt is thought to relate to poor emotional control and game performance.Despite widespread recognition of tilt in video gaming, there is a lack of research examining tilt empirically.1007 gamers took part in our online study examining gamers experience of tilt, the factors which contribute to and protect against tilt, and the emotion regulation strategies gamers employ to deal with tilt. Gamers who reported playing for more competitive reasons, were at higher risk of experiencing tilt. Factors associated with an increased risk of experiencing tilt were increased anger and more hours spent playing. Protective factors against experiencing tilt were also identified, inclusive of a greater number of years gaming experience and engagement in adaptive emotion regulation strategies. This study provides an important starting point for creating a better understanding of tilt in gaming, equipping us with new knowledge to better support gamers to improve their emotion regulation during game play performance.